RESILIENCE OF SALAF ISLAMIC BOARDING SCHOOLS EDUCATION DURING A PANDEMIC: A Case Study of the Live Ngaos Kitab Kuning Program - Albaburrahim, Albaburrahim; Alatas, Mochamad Arifin; Putikadyanto, Agus Purnomo Ahmad (Islamuna: Jurnal Studi Islam, 2022)
ABSTRACT This research is motivated by the demands of Salaf Islamic boarding school education to survive in the face of covid-19. The purpose of this study is to describe the educational resilience of Salaf Islamic Boarding Schools during the pandemic through the live Ngaos Kitab kuning program. The method in this research is descriptive qualitative. Data collection techniques by observation, interviews, and documentation. The results of this study include the stages of preparation, implementation, and benefits of the live ngaos Kitab kuning program at the Salaf Islamic Boarding School in PPAH. 1) The stages of preparation include: Formation of the technical team of students, live facilities and infrastructure and live program. 2) The implementation stages include: setting the place, setting the sound, setting the picture, and the live recording process. 3) The benefits of the program include: students can complete the lack of meaning, students are accustomed to ngaos wherever and whenever, show that the existence of salaf pesantren can transform in technological progress, and Islamic da'wah media in distance learning. Thus, education in salaf Islamic boarding schools is able to survive during the pandemic through the live ngaos kuning program. ABSTRAK Penelitian ini dilatarbelakangi adanya tuntutan pendidikan pondok pesantren salaf bertahan dalam menghadapi covid-19. Adapun tujuan penelitian ini untuk mendeskripsikan resiliensi pendidikan pondok pesantren salaf pada masa pandemi melalui program live ngaos kitab kuning. Metode dalam penelitian ini adalah deskriptif kualitatif. Hasil penelitian ini meliputi tahapan persiapan, pelaksanaan, dan manfaat program live ngaos kitab kuning pondok pesantren salaf di PPAH. 1) Tahapan persiapan meliputi: Pembentukan tim teknis santri, sarana dan prasarana live dan program live. 2) Tahapan pelaksanaan meliputi: setting tempat, setting suara, setting gambar, dan proses rekaman live. 3) Manfaat program meliputi: santri dapat melengkapi kekurangan pemaknaan, santri terbiasa ngaos di manapun dan kapanpun, menunjukkan eksistensi pesantren salaf bisa bertranformasi dalam kemajuan teknologi, dan sebagai media dakwah Islam dalam pembelajaran jarak jauh. Dengan demikian, pendidikan dalam pondok pesantren salaf mampu bertahan pada masa pandemi melalui program live ngaos kitab kuning.